2020
DOI: 10.1371/journal.pone.0229541
|View full text |Cite
|
Sign up to set email alerts
|

Association of combination statin and antihypertensive therapy with reduced Alzheimer’s disease and related dementia risk

Abstract: BackgroundHyperlipidemia and hypertension are modifiable risk factors for Alzheimer's disease and related dementias (ADRD). Approximately 25% of adults over age 65 use both antihypertensives (AHTs) and statins for these conditions. While a growing body of evidence found statins and AHTs are independently associated with lower ADRD risk, no evidence exists on simultaneous use for different drug class combinations and ADRD risk. Our primary objective was to compare ADRD risk associated with concurrent use of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 55 publications
(57 reference statements)
1
46
0
Order By: Relevance
“…AD (Zhuang et al, 2016). A more recent retrospective cohort study found that ARBs combined with statins reduced AD more than statins combined with non-RAS-acting antihypertensives (Barthold et al, 2020). Consistent with previous studies, ARBs were found to be more effective than ACEIs in reducing dementia risk.…”
Section: Studies Showing Positive Effects On Cognition and Neural Prosupporting
confidence: 65%
See 1 more Smart Citation
“…AD (Zhuang et al, 2016). A more recent retrospective cohort study found that ARBs combined with statins reduced AD more than statins combined with non-RAS-acting antihypertensives (Barthold et al, 2020). Consistent with previous studies, ARBs were found to be more effective than ACEIs in reducing dementia risk.…”
Section: Studies Showing Positive Effects On Cognition and Neural Prosupporting
confidence: 65%
“…Furthermore, a meta-analysis of studies on AD and aging showed that ARBs have a protective role in the risk of cognitive impairment of aging and AD, while both ACEIs and ARBs have benefits on prevention of AD ( Zhuang et al, 2016 ). A more recent retrospective cohort study found that ARBs combined with statins reduced AD more than statins combined with non-RAS-acting antihypertensives ( Barthold et al, 2020 ). Consistent with previous studies, ARBs were found to be more effective than ACEIs in reducing dementia risk.…”
Section: Renin-angiotensin System-acting Drugsmentioning
confidence: 99%
“…The association between the PON1 enzyme and the development of AD was described in the late 1990s [ 188 , 189 ]. In addition, treatment with statins have shown to improve the cognitive function in patients with AD [ 190 , 191 , 192 , 193 ]. Paraoxonases-1 and -2 are expressed in the human frontal cortex [ 194 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, disruption of cholesterol homeostasis has been associated with AD pathogenesis [ 22 , 23 , 24 ]. Early epidemiological studies reported a lower risk of dementia in patients under statin treatment [ 25 , 26 ] and, more recently, a combination of statins and antihypertensive drugs was shown to be more effective in reducing the risk of AD and related dementias [ 22 ]. Statins reduce cholesterol by inhibiting its biosynthesis at a critical rate-limiting step in the mevalonate pathway, i.e., by blocking the activity of HMG-CoA (5-hydroxy-3-methylglutaryl coenzyme A) reductase in the liver.…”
Section: Introductionmentioning
confidence: 99%